Interior of Mechanics Hall during demolition, Huntington Avenue, January 11, 1961 - Shwachman, Irene (Tufts Archival Research Center, 2005)
Street-level view of the interior of Mechanics Hall under demolition. Debris is seen on the floor and interior structures are still partially standing as well as the roof trusses. 10 7/8 x 11 1/4 overall 10 15/16 x 11 11/16 Photographs